Diagnostics and resolution of problems of interaction between government and business in the socio-economic development of the Stavropol territory - O. N. Momotova; G. V. Vorontsova; R. M. Ustaev; N. P. Kharchenko; O. M. Meshcheryakova (Вестник Северо-Кавказского федерального университета)
Based on a retrospective analysis of indicators characterizing the socio-economic development of the region, the authors of the article give an indirect assessment of the level of interaction between government and business and identify problems of interaction. The research team presents a generalization of the current state of digitalization of issues of interaction between government and business in the Stavropol Territory and is proposed as one of the ways to improve the tools for digital interaction – the use of integration mechanisms in platform solutions, in particular the creation of a personal account of an entrepreneur using artificial intelligence technologies.